2023
DOI: 10.1093/hr/uhad136
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, population structure, and genome-wide association analysis of ginkgo cultivars

Abstract: Ginkgo biloba is worldwide an economically valuable tree. The species has nearly got extinct during the Quaternary which likely result in reduction of its genetic variability. This is now conserved in few natural populations in China and number of cultivars which are, however, derived from a few ancient trees, helping the species survival in China through medieval times. Despite the recent interest on ginkgo, however, the detail knowledge of its genetic diversity, conserved in cultivated trees and cultivars re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…2E ; Supplementary Data Figs S10 and S11 ), indicating a higher level of inbreeding in C. gigantea . Using a threshold for ROH length of >1 Mb to evaluate recent inbreeding levels [ 15 , 22 ], we found that 0.2198% of the C. gigantea and 0.1171% of the C. duclouxiana genome consisted of such long ROH regions ( Fig. 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…2E ; Supplementary Data Figs S10 and S11 ), indicating a higher level of inbreeding in C. gigantea . Using a threshold for ROH length of >1 Mb to evaluate recent inbreeding levels [ 15 , 22 ], we found that 0.2198% of the C. gigantea and 0.1171% of the C. duclouxiana genome consisted of such long ROH regions ( Fig. 2E ).…”
Section: Resultsmentioning
confidence: 99%
“…Chrysanthemum is a complex species with high heterozygosity (>3%), high repetitiveness (>80%), huge genome size (8.47–9.02 Gb) [ 9 ], rapid decay rate, and a relatively low gene density of approximately one gene per 58.74 kb, which makes it rather challenging to identify causal genes underlying the detected association loci within a relatively narrow genomic region. It has been documented that a wide range of 100 kb region centered on the peak SNPs has been employed to explore candidate genes in species with rapid decay rate, such as ginkgo [ 55 ] and apple [ 56 ]. Therefore, to overcome the challenge of candidate gene identification in chrysanthemum GWAS, a relatively less stringent range of 100 kb upstream and downstream of the significant SNPs was first used to detect the putative candidate genes, and then we combined the RNA-seq data and qRT–PCR analyses to verify the candidate genes responsible for PH traits.…”
Section: Discussionmentioning
confidence: 99%
“…The sequencing original data from the Illumina platform were screened through FASTP software (version 0.18.0). Reads with unknown nucleotides (N) ≥ 10%, Phred quality score ≤ 20 with more than 50% base content and those containing connectors were excluded [ 65 ]. Subsequently, the filtered reads were compared to the reference genome using the software BWA (version 0.7.12).…”
Section: Methodsmentioning
confidence: 99%